СOMPOSITION AS A WORD-FORMING TYPE AND ITS CONNECTION WITH INCORPORATING: ANALYSIS OF OCCASIONALISMS IN THE POETRY OF V.V. MAYAKOVSKY AND THE PROBLEMS OF INTERLINGUISTIC TRANSFORMATION (RUSSIAN - UZBEK) - Marina A. Kim (Bright Mind Publishing, 2026)
Background: The article examines the issues of comparison of word formation of compound words and incorporation. The problems of correspondence and difference of these two linguistic processes in linguistics are raised. Compound words are examined on examples of occasionalisms taken from the lyrical works of V.V. Mayakovsky. A detailed lexical, word-formation, stylistic functional analysis of occasionalisms-composites is given in order to find a connection between the concepts of these two concepts.
Keywords: Incorporation, occasionalisms, V.V. Mayakovsky, lexical composition, composites, context, word formation, morphology, poetics, semantics.